Numerical simulation of Ca(2+) "Sparks" in skeletal muscle - Jiang, YH (1999)
A three dimensional (3D) model of Ca(2+) diffusion and binding within a sarcomere of a myofibril, including Ca(2+) binding sites troponin, parvalbumin, sarcoplasmic reticulum Ca(2+) pump, and fluorescent Ca(2+)-indicator dye (fluo-3), was developed to numerically simulate laser scanning confocal microscope images of Ca(2+) "sparks" in skeletal muscle. Diffusion of free dye (D), calcium dye (CaD), and Ca(2+) were included in the model. The Ca(2+) release current was assumed to last 8 ms, to arise within 4 x 10(-5) &mgr;m(3) at the triad and to be constant during release. Line scan confocal fluorescence images of Ca(2+) sparks were simulated by 3D convolution of the calculated distribution of CaD with a Gaussian kernel approximating the point spread function of the microscope. Our results indicate that the amplitude of the simulated spark is proportional to the Ca(2+) release current if all other model parameters are constant. For a given release current, the kinetic properties and concentrations of the binding sites and the diffusion parameters of D, CaD, and Ca(2+) all have significant effects on the simulated Ca(2+) sparks. The simulated sparks exhibited similar amplitudes and temporal properties, but less spatial spread than experimentally observed sparks.